ERILAKU PEMENUHAN KEBUTUHAN HIDUP PENGEMIS DI PERKOTAAN (STUDI TENTANG BUDAYA KEMISKINAN PENGEMIS DI KABUPATEN KARIMUN) - Muhammad Nofrizal; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Poverty occurs not only because of the weakness of the community in accessing the opportunities they have. So that poverty grows because of the undeveloped culture and work ethic in the community itself. Weak mental attitude, low education, and laziness try to make them look for instant ways to make ends meet, so they work in the informal sector as beggars. Culture of poverty pattern of beggars in Karimun Regency. This research was conducted in Karimun. The purpose of this study is to find out the background of the life of beggars and the behavior of beggars in meeting their needs. In determining the informants using purposive sampling technique. The number of informants in this study were five people. The theory used is the theory of poverty culture by Oscar Lewis to identify the form of a culture of poverty found in beggars in Karimun. The results obtained are a form of culture that is passed down from generation to generation. These cultures include dependence on the agent, short childhood, low participation and integration in community institutions. Keywords: Culture of Poverty, Poverty, Beggars